2018
DOI: 10.1021/jacs.7b13776
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Amino Alkoxide–Evans Enolate Mixed Aggregates: Aldol Addition with Matched and Mismatched Stereocontrol

Abstract: Building on structural and mechanistic studies of lithiated enolates derived from acylated oxazolidinones (Evans enolates) and chiral lithiated amino alkoxides, we found that amino alkoxides amplify the enantioselectivity of aldol additions. The pairing of enantiomeric series affords matched and mismatched stereoselectivities. The structures of mixed tetramers showing 2:2 and 3:1 (alkoxide-rich) stoichiometries are determined spectroscopically. Rate and computational studies provide a viable mechanistic and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 77 publications
1
9
0
1
Order By: Relevance
“…[ 6 Li]­LDA and [ 6 Li, 15 N]­LDA were isolated as LiCl-free solids . Solvation was probed in several ways, including by using pyridine as a 6 Li chemical shift reagent and [ 15 N]­isoquinoline (eq ) as an inexpensive, relatively nonvolatile pyridine surrogate. …”
Section: Resultsmentioning
confidence: 99%
“…[ 6 Li]­LDA and [ 6 Li, 15 N]­LDA were isolated as LiCl-free solids . Solvation was probed in several ways, including by using pyridine as a 6 Li chemical shift reagent and [ 15 N]­isoquinoline (eq ) as an inexpensive, relatively nonvolatile pyridine surrogate. …”
Section: Resultsmentioning
confidence: 99%
“…An important mechanistic study by Jermaks et al reported that aldolic additions to isobutyraldehyde provided high selectivity and high yields (Scheme ). By analyzing structural and mechanistic information about lithium enolates derived from acylated oxazolidinones (Evans' enolates) and chiral lithiated aminoalkoxides, the authors found that aminoalkoxides enhance the enantioselectivity of aldol additions.…”
Section: Discussionmentioning
confidence: 99%
“…Thed issociated, significantly more stable n-BuLi (compared to 3 Ce )a cts as ab ase,d eprotonating unreacted ketone at the a-position of the carbonyl moiety.T his competitive reaction path reflects the main part of the recovered ketone,a slisted in Table 1, since aqueous workup will involve keto-enol tautomerism. Complex 7 features acommon structural motif in lithium alkoxide complexes [55][56] with the lithium and alkoxy oxygen atoms occupying alternating positions of ac ube.T he lithium atoms are saturated with one THF molecule each.…”
Section: Methodsmentioning
confidence: 99%